2022
DOI: 10.1177/09603271221093635
|View full text |Cite
|
Sign up to set email alerts
|

MFGE8 decreased neuronal apoptosis and neuroinflammation to ameliorate early brain injury induced by subarachnoid hemorrhage through the inhibition of HMGB1

Abstract: Aim Both MFGE8 and HMGB1 were vital players for aneurysmal subarachnoid hemorrhage. However, whether HMGB1 was served as the downstream target of MFGE8 was unknown. To test this new mechanism, we performed the SAH model in rats. Method All treatments were injected intraventricularly into the right lateral ventricles. SAH grade, brain water content, and neurological function scores were evaluated. HMGB1 expression was studied by double immunofluorescence staining. HE and Nissl’s staining were performed to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition to this anti-inflammatory role, Mfge8 also plays a protective role in regulating adult stem cell populations (Y. Zhou et al, 2018) and is neuroprotective under a variety of injury and inflammatory states (e.g., stroke, prion diseases, neurodegeneration, brain injury (Chen et al, 2019; Choi et al, 2020; Gao et al, 2021; Kranich et al, 2010; Li et al, 2019; Qiu et al, 2022; J. Wang et al, 2021; Xiao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this anti-inflammatory role, Mfge8 also plays a protective role in regulating adult stem cell populations (Y. Zhou et al, 2018) and is neuroprotective under a variety of injury and inflammatory states (e.g., stroke, prion diseases, neurodegeneration, brain injury (Chen et al, 2019; Choi et al, 2020; Gao et al, 2021; Kranich et al, 2010; Li et al, 2019; Qiu et al, 2022; J. Wang et al, 2021; Xiao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…After a SAH, HMGB1, released from necrotic neurons, could induce cytokine release and leukocyte recruitment and then trigger the inflammatory response after interaction with TLR4 and the receptor for advanced glycation end products (RAGEs) [ 69 ]. Experimental animal studies have revealed that the inhibition of HMGB1 could mitigate an inflammatory response and ameliorate EBI after a SAH [ 70 , 71 , 72 ]. Moreover, clinical research suggests that the serum HMGB1 of SAH patients may serve as an independent biomarker predictive of DCI [ 73 ].…”
Section: The Therapeutic Role Of Sirt1 In Sahsmentioning
confidence: 99%
“…Milk fat globule epidermal growth factor 8 (MFG-E8) is a glycoprotein which mediates phagocytosis of apoptotic cells [ 29 ], that has recently been implicated in diminishing the inflammatory response [ 30 ]. One recent study employed the use of a recombinant MFG-E8 in a SAH rat model and discovered that MFG-E8 downregulated the proinflammatory HMGB1 and attenuated early brain injury caused by subarachnoid hemorrhage (SAH) [ 31 ]. Indeed, targeting the proinflammatory HMGB1 is a focus of recent work and has been shown to diminish early brain injury following SAH [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%